PENGARUH KOMUNIKASI DAN PENGEMBANGAN KARIR TERHADAP PRODUKTIVITAS KERJA KARYAWAN BANK BPR NBP 18 - Enri Hotmaida Rumapea; Dedi Koko Herianto; Mangasi Sinurat; Imelda Mardayanti (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to analyze the influence of communication and career development on the work productivity of employees at Bank BPR NBP 18. The research is motivated by the unachieved work productivity targets of Account Officers during the period of July–December 2025, which indicates the need to identify factors affecting work productivity. This study employs a quantitative approach using a survey method. The research population consists of 36 Account Officers at Bank BPR NBP 18, with the sampling technique using the census method so that the entire population is used as respondents. Data were collected through questionnaires and analyzed using classical assumption tests, coefficient of determination, and hypothesis testing using the t-test and F-test. The results indicate that communication has a positive and significant effect on work productivity. Similarly, career development has a positive and significant effect on work productivity. Simultaneously, communication and career development have a significant effect on work productivity, which indicates that both variables together are able to explain the variation in employee work productivity. Keywords: Communication, Career Development, Work Productivity, Rural Bank (BPR).   Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh komunikasi dan pengembangan karir terhadap produktivitas kerja karyawan Bank BPR NBP 18. Penelitian dilatarbelakangi oleh belum tercapainya target produktivitas kerja Account Officer selama periode Juli–Desember 2025, yang mengindikasikan perlunya identifikasi faktor-faktor yang memengaruhi produktivitas kerja. Penelitian menggunakan pendekatan kuantitatif dengan metode survei. Populasi penelitian terdiri atas 36 Account Officer Bank BPR NBP 18, dengan teknik pengambilan sampel menggunakan metode sensus sehingga seluruh populasi dijadikan responden. Data dikumpulkan melalui kuesioner dan dianalisis uji asumsi klasik, koefisien determinasi dan pengujian hipotesisi menggunakan uji t dan uji F. Hasil penelitian menunjukkan bahwa komunikasi berpengaruh positif dan signifikan terhadap produktivitas kerja, pengembangan karir berpengaruh positif dan signifikan terhadap produktivitas kerja, Secara simultan, komunikasi dan pengembangan karir berpengaruh signifikan terhadap produktivitas kerja, yang mengindikasikan bahwa kedua variabel tersebut secara bersama-sama mampu menjelaskan variasi produktivitas kerja karyawan. Kata kunci: Komunikasi, Pengembangan Karir, Produktivitas Kerja, Bank Perkreditan Rakyat.